Technical guidance on the use of Sengon and Jabon Logging Waste as Renewable Fuel to increase the Economic Value of the Andalambe Village Forest Farmers Group, Konawe, Indonesia - Niken Pujirahayu; Zakiah Uslinawaty; Sitti Noorbaini Sarmin; Nurrohana Ahmad; Lies Indriyani; Sahindomi Bana; Basrudin; Nurhayati Hadjar; Agus Setiawan; abigael Kabe; Nurnaningsih Hamzah; Aura Charismailliah; Alfan Ananta Julianda; La Ode Muh. Jaffar Efendi (International Journal of Community Service (IJCS), 2026)
The International Collaborative Community Service Program, conducted by the Forestry Study Program of the Faculty of Forestry and Environmental Sciences in collaboration with the University of Technology of Mara, Malaysia, aims to: Provide training on utilizing sengon/jabon wood waste (harvested) by converting it into wood pellets as a renewable energy source; and Increase the economic value of community forests by improving the quality of primary wood and creating value-added products from waste. This community service activity is implemented through outreach and practical training on making wood pellets from sengon/jabon waste, introducing the potential of wood waste as a renewable energy source. Techniques for collecting, drying, and shredding wood waste, as well as the process of molding the shredded waste into pellets, are also covered. After this activity, community forest farmer groups can utilize and convert previously unused waste from sengon and jabon felling into wood pellet products. Environmental benefits include more sustainable forest management and reduced wood waste, which can otherwise pollute the environment. The expected benefits for the partner (UiTM) include applying existing knowledge and technology in the context of international community service and strengthening collaborative networks.